Arañas terafósidas de Costa Rica (Araneae: Theraphosidae). II. Psalmopoeus reduncus, redescripción, distribución y el problema de dispersión en terafósidas - Valerio G., Carlos E. (1979)
Psalmopoeus reduncus (Karsh) is redescribed and illustrated. These spiders live in tree holes up to 4 m above ground level in the forest. Females have been found with eggs in March and April, males wander about in December. The species shows large variation in bulb and leg length, probably correlated with their wide distribution. Poor dispersal mechanisms in the theraphosids in general restrict distribution to small geographical areas, but the arboreal habits of this particular species apparently permit dispersal by phoresis on birds. Avicularia avicularia (L) is reported from Costa Rica for the first time.